1967
DOI: 10.1111/j.2044-8260.1967.tb00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Religious Belief and Co‐education in a Sample of Sixth‐Form Boys and Girls

Abstract: A sample of 2,276 boys and girls in the sixth forms of English grammar-schools completed a questionnaire which included items on religious belief and practice. Results indicate that the incidence of belief is lower than in the adult population, though reported frequency of church-going is higher. Grounds are offered for thinking that the several indices of belief and practice may not be functionally equivalent. Boys are less religious than girls, and have a less benevolent conception of God. Girls in co-educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Previous research has, however, demonstrated that pupil attitudes towards religion are related to a number of other variables. These variables are sex and age (Garrity, 1966;Povall, 1971), intelligence (Hyde, 1959), religious behaviour (Johnson, 1966), parental religious behaviour (Greer, 1971), socio-economic background (Jones, 1962), the geographical location of the school (Alves, 1968), and the co-educational or single sex status of the school (Wright and Cox, 1967). Since these variables may contaminate the influence of the school on pupil attitudes they must be taken into consideration in the research design.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has, however, demonstrated that pupil attitudes towards religion are related to a number of other variables. These variables are sex and age (Garrity, 1966;Povall, 1971), intelligence (Hyde, 1959), religious behaviour (Johnson, 1966), parental religious behaviour (Greer, 1971), socio-economic background (Jones, 1962), the geographical location of the school (Alves, 1968), and the co-educational or single sex status of the school (Wright and Cox, 1967). Since these variables may contaminate the influence of the school on pupil attitudes they must be taken into consideration in the research design.…”
Section: Introductionmentioning
confidence: 99%
“…The rich source of quantitative data provided by Cox's study could answer many more focused questions than were containable within his book Sixth Form Religion. Two subsequent papers explored the relationship between coeducation and religious belief (Wright & Cox, 1967a) and between moral judgement and religious belief (Wright & Cox, 1967b).…”
Section: Sixth-form Religionmentioning
confidence: 99%
“…Research evidence suggests that students' attitudes toward religion are influenced by gender, age, religious behavior, and parents' religious behavior (Francis and Kay 1984;Greer 1971;Wright and Cox 1967). The vast majority of studies about attitude toward Christianity have been conducted in the United Kingdom with studies investigating the influence of age (Francis 1989a), location (Gibson and Francis 1989;Greer and Francis 1991), school type (Boyle and Francis 1986), Christian tradition (Greer and Francis 1990), and Catholic identity (Curran and Francis 1996).…”
Section: Attitude Toward Christianitymentioning
confidence: 99%